Efektivitas LKS Berbasis KPS Materi Asam-basa dalam Meningkatkan KPS dan Sikap Ilmiah - Wahyu Arif Furqon; Noor Fadiawati; Nina Kadaritna (Universitas Lampung, 2018)
This research was aimed to describe the effectiveness of acid-base student worksheets based-on SPS to increase students SPS and scientific attitudes. The design of this research was the matching only pretest and posttest control group design. The population of this research was all of students XI science at SMAN 16 Bandarlampung in academic year2016-2017. The sample of research were class XI IPA 4 and XI IPA 6. Instrument in this research were students worksheets based on SPS and conventional student worksheets, pretest and postest, questions and attitude assessment sheets. t test results of average n-gain value showed that student SPS applied by using worksheets based-on SPS is higher than the average n-gain of students' SPS with conventional learning. Science Attitudes of the student also increased, It can be concluded that implementation of student worksheets based-on SPS was effective to increase students SPS and scientific attitudes in the learning of acid and bases topic.Penelitian ini bertujuan untuk mendeskripsikan efektivitas LKS berbasis KPS dalam meningkatkan KPS dan sikap ilmiah siswa pada materi asam-basa. Desain penelitian ini adalah the matching only pretest-postest control group design. Populasi pada penelitian ini adalah seluruh siswa kelas XI IPA SMA Negeri 16 Bandarlampung tahun pelajaran 2016-2017. Sample penelitian adalah kelas XI IPA 4 dan XI IPA 6. Instrumen yang digunakan yaitu LKS berbasis KPS, LKS konvensional, soal pretes dan postes serta lebar penilaian sikap. Hasil uji t terhadap rata-rata n-gain KPS siswa pada materi asam-basa yang diterapkan pembelajaran menggunakan LKS berbasis KPS lebih tinggi daripada rata-rata n-gain keterampilan proses sains siswa dengan pembelajaran menggunakan LKS konvensional. Sikap ilmiah juga meningkat, sehingga dapat disimpulkan pembelajaran dengan LKS berbasis KPS efektif dalam meningkatkan KPS dan sikap ilmiah siswa pada materi asam-basa.Kata kunci: asam-basa, sikap ilmiah, KPS, LKS